2021
DOI: 10.1093/ckj/sfaa273
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training in dialysis patients: impact on cardiovascular and skeletal muscle health

Abstract: Dialysis patients show a high rate of reduced functional capacity, morbidity and mortality. Cardiovascular disorders, muscle atrophy and malnutrition, play an essential role among the etiological factors. Sedentary life characterizes them and contributes to the aggravation of these disorders. On the contrary, exercise training is an important preventive and therapeutic tool both for cardiovascular problems and for the appearance of muscle atrophy in dialysis patients. Regular exercise causes both central (card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 78 publications
1
23
0
Order By: Relevance
“…Moreover, none of the trials explored the impact on sarcopaenia as assessed by EWGSOP2, which was published in 2019. More recent reviews have emphasized the benefits of exercise training, although they were not limited to intradialytic exercise [ 40 , 41 ]. Again, the age range of the studies was either not mentioned [ 40 ] or ranged from 36 to 71 years [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, none of the trials explored the impact on sarcopaenia as assessed by EWGSOP2, which was published in 2019. More recent reviews have emphasized the benefits of exercise training, although they were not limited to intradialytic exercise [ 40 , 41 ]. Again, the age range of the studies was either not mentioned [ 40 ] or ranged from 36 to 71 years [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recent reviews have emphasized the benefits of exercise training, although they were not limited to intradialytic exercise [ 40 , 41 ]. Again, the age range of the studies was either not mentioned [ 40 ] or ranged from 36 to 71 years [ 41 ]. Thus, although the authors concluded that there is convincing evidence that exercise training improves physical function measured as aerobic capacity, muscle endurance strength and balance at all ages and all stages of CKD [ 41 ], in fact, the evidence so far is thin regarding the age range of participants in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Increased phosphorylation of mRNA translational signalling proteins due to RE and whey protein intake leads to enhanced protein synthesis in untrained individuals. In addition, ingestion of whey protein after RE activates the mTOR signalling pathway in a dose-dependent manner [63]. Supplementing PE with proper energy sources such as carbohydrates, protein, vitamins and iron will help keep muscle protein breakdown under control.…”
Section: Nutritionmentioning
confidence: 99%
“…As a result of reduced sympathetic tone, these beneficial adaptations may be due to increased parasympathetic activity, decreased catecholamine levels, and decreased endogenous cardiac output stimulation. PE, particularly the AE, raises resting vagal tone while lowering sympathetic tone in both healthy people and those with kidney disease [63].…”
Section: Cardiovascular Functionmentioning
confidence: 99%
“…ESKD causes a considerable financial burden to society [ 14 ]. In ESKD receiving hemodialysis, cardiovascular disease is a major cause of death (42%) due to secondary complications [ 15 - 17 ]. Despite advances in dialysis technology, cardiovascular mortality of these patients remains high.…”
Section: Introductionmentioning
confidence: 99%